GNSS receiver ionospheric scintillation data processing - Wang, Lanlan (2014)
As an advanced measurement tool and new productivity, GNSS has been integrated into various application areas of social development. However, ionospheric scintillation reduces the positioning accuracy of GNSS. Therefore, it is necessary to study the morphology of ionospheric scintillation. Using the observation data (Mar. 2012 Oct. 2013), a morphological analysis for ionospheric scinitillation over Singapore area has been performed. The intensity of scintillation in L2 is near 1.45 times of intensity in L1 when scintillation is weak, and times change with the intensity of scintillation. S4 depicts amplitude scintillation more clearly than SI. vTEC reaches its maximum after the noon and reaches minimum in the morning. The maximum of vTEC in equinox months is much more than that in June and July. The occurrence rate, intensity and duration are evidently enhanced in equinox months, and are evidently reduced in June, July, November and December. Scintillation appears in the night, hardly happens in the day. The onset time of scintillation with the peaks is earliest in March, April, September and October, and has a time delay in November and December, and the latest is in November and December, nearly in the midnight. Because of different modulation mode, GLONASS has a stronger anti-interference ability than GPS.